ANALISIS PEMBERIAN PINJAMAN KREDIT PADA KOPERASI WAHANA ARTHA SELARAS BANDAR LAMPUNG - Asyari Ilyas (GEMA : Jurnal Gentiaras Manajemen dan Akuntansi, 2014)
The problems studied in this research is: How does the lending process in Credit UnionsWARAS Sukarame, Bandar Lampung? And how do these compare in Kopdit WARAS lendingSukarame, Bandar Lampung with Credit Unions Act standards in Indonesia? The objective of thisstudy was to analyze the lending process conducted by the Cooperative Credit rides conformableSukarame Artha, Bandar Lampung and analyze comparisons between the lending Credit UnionsArtha conformable Sukarame rides, Bandar Lampung to the standard Law Credit Unions inIndonesia.From the analysis, the analysis process of granting loans to members who apply CreditUnions Sukarame WARAS, Bandar Lampung preparation of terms of credit that is already wellunderway with obtaining needed information Credit Unions of members who would apply for loansand credit decisions are decided by the credit committee, through direct mail and delivered bymembers who will apply for a loan. Function analysis of the feasibility of using the principle ofborrowing already 5C and TUKKEPAR.